Downside Risk - Ang, Andrew; Chen, Joseph; Xing, Yuhang (Review of Financial Studies, 2006)
Economists have long recognized that investors care differently about downside losses versus upside gains. Agents who place greater weight on downside risk demand additional compensation for holding stocks with high sensitivities to downside market movements. We show that the cross section of stock returns reflects a downside risk premium of approximately 6% per annum. Stocks that covary strongly with the market during market declines have high average returns. The reward for beasring downside risk is not simply compensation for regular market beta, nor is it explained by coskewness or liquidity risk, or by size, value, and momentum characteristics.